2007
DOI: 10.1111/j.1471-0528.2007.01527.x
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study over 5 to 10 years of clinical outcomes in women with idiopathic detrusor overactivity

Abstract: Objective To evaluate the long-term clinical outcome in women with idiopathic detrusor overactivity (IDO) and to identify significant prognostic factors.Design Longitudinal study incorporating retrospective case note review and a postal questionnaire.Setting Tertiary referral urogynaecology clinic in Australia.Population Women with a sole urodynamic diagnosis of IDO.Methods Audit of urodynamic records and case notes. Postal questionnaire incorporating validated disease-specific qualityof-life (QoL) instruments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 13 publications
(30 reference statements)
0
17
0
Order By: Relevance
“…A significant proportion of women have a suboptimal response to treatment; an Australian study showed that after 10 years of attending a specialist incontinence clinic, only 30% of women showed improvement. 19 A small retrospective study of 100 patients attending our clinic over the past 12 years showed similar results; 62% of the women claimed that their condition was unimproved or worse. This has prompted research into novel treatment strategies in women with OAB in our department over the past 15 years.…”
Section: Urogynaecologymentioning
confidence: 56%
“…A significant proportion of women have a suboptimal response to treatment; an Australian study showed that after 10 years of attending a specialist incontinence clinic, only 30% of women showed improvement. 19 A small retrospective study of 100 patients attending our clinic over the past 12 years showed similar results; 62% of the women claimed that their condition was unimproved or worse. This has prompted research into novel treatment strategies in women with OAB in our department over the past 15 years.…”
Section: Urogynaecologymentioning
confidence: 56%
“…However, symptoms due to IDO were not addressed in that study. A more recent study [11] considered the medium‐term symptomatic follow‐up of women with IDO but did not consider repeat UDS, and involved fewer participants than the present study. There have been longitudinal community‐based questionnaire studies that considered LUTS and incontinence in women over time [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with 8 mg fesoterodine showed significant improvements (compared with placebo) in 8 of the 9 domains assessed by the King’s Health Questionnaire. While 4 mg fesoterodine (and tolterodine 4 mg), showed significant improvements (compared with placebo) in 7 of the 9 domains 59. The domains where fesoterodine was associated with improvement include: severity/coping, emotions, role limitations, physical limitations, social limitations, sleep/energy, personal relationship and incontinence impact 56,57.…”
Section: Efficacy Of Fesoterodine and Tolterodine In Clinical Trialsmentioning
confidence: 98%
“…While muscarinic antagonists can be used to effectively treat OAB in approximately 65% of patients, numerous patients discontinue therapy long term due to adverse events including dry mouth and constipation 59. These adverse events occur due to a lack of organ selectivity of antimuscarinic agents60 as muscarinic receptors are not only located on the detrusor muscle but also in the salivary glands61 and smooth muscle of the gastrointestinal tract 13,62.…”
Section: Adverse Events Associated With Fesoterodine and Tolterodinementioning
confidence: 99%